Impact of Pseudomonas aeruginosa quorum sensing signaling molecules on adhesion and inflammatory markers in endothelial cells - Curutiu, Carmen; Iordache, Florin; Lazar, Veronica; Pisoschi, Aurelia Magdalena; Pop, Aneta; Chifiriuc, Mariana Carmen; Hoban, Alina Maria (Beilstein Journal of Organic Chemistry, 2018)
Pseudomonas aeruginosa relies on the quorum sensing (QS) signaling system as a central regulator mechanism of virulence expression that contributes to the formation and maintenance of biofilms and tolerance to conventional antimicrobials. QS Signaling molecules (QSSMs) may be recognized and may function also within the host cells, being potentially involved in the progression of the infectious process. In this study we evaluate the expression of adhesion and inflammatory molecules in endothelial cells treated with P. aeruginosa QSSMs, in order to bring new insights on the mechanisms involved in the interaction of P. aeruginosa with host cells during the infectious process. Endothelial cells were stimulated with 20 µM of main P. aeruginosa QSSMs (OdDHL = N-(3-oxododecanoyl)-L-homoserine lactone, C4HSL = N-butyryl-L-homoserine lactone, PQS = 2-heptyl-3-hydroxy-4(1H)-quinolone and HHQ = 2-heptyl-4-quinolone). Adherence to endothelial cells, inert substratum and biofilm formation was evaluated. The expression of adhesion molecules (VE-cadherin, PECAM-1, ICAM-1, and P-selectin) and inflammatory response molecules (IL-1β, IL-6, TNFα, TGFβ, and eNOS) was assessed by qRT-PCR and flow cytometry. Our results showed that bacterial adherence to inert substratum and biofilm were decreased in the presence of all tested QSSMs. The adherence index of PAO1 laboratory strain to host cells was decreased between 10–40% in the presence of QSSMs, as compared to untreated control. Expression of eukaryotic cells adhesion molecules ICAM-1 and P-selectin was stimulated by QSSMs, whereas VE-cadherin and PECAM-1 levels were increased only by C4HSL. The inflammatory response of endothelial cells was also modulated, as observed by the modified expression of IL-1β (for C4HSL, PQS and HHQ), IL-6 (for C4HSL and HHQ), TNFα (for C4HSL and HHQ), TGFβ, and eNOS factors. Our results demonstrate that the main pseudomonadal QSSMs differentially modulate endothelial cells adhesion and proinflammatory cytokine expression. These observations provide new insights in the mechanisms by which different QSSMs activate endothelial cells and modulate the infectious process, and support the importance of recent studies aiming to develop anti-QS therapeutic strategies to fight against P. aeruginosa infections.
Keywords: adhesion; host–pathogen interaction; inflammation; Pseudomonas; quorum sensing